Effects of different biochars, compost and lime treatments on the chemical properties of sandy soils - Holes, Annamária; Szegi, Tamás; Fuchs, Márta; Gulyás, Miklós; Aleksza, László (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2014)
Decrease in organic matter of the soil is one of the major threats to soils in Europe and other parts of the globe. Maintaining or increasing organic carbon is a great challenge in agricultural practices. Application of composts and other organic amendments is an important way of compensation of losses of organic carbon at the same time it is solving the placement and recycling of organic wastes and residues.The favorable effect of these amendments on physical, chemical and biological properties has been proved by different studies, however the stability and the rate of the influence is an issue that can be improved.The aim of the presented study was to investigate the effect of carbonates on the solubility of applied organic materials and selected soil parameters.Different biochars, compost and carbonate were added to light textured soil. The pH and E4/E6 rates were studied under laboratory conditions.Beside the increase of soil organic matter content, all studied parameters gave promising results. The decrease in E4/E6 rate suggests that the inorganic carbonates are stabilizing the fresh organic residues and prevent the leaching processes. Improved soil organic carbon stability is very important in light textured soils.Further investigations are undergoing to determine the optimal rate of components and extend the kinds of material available for application.
Keywords: biochar; compost; sand; soil; biodegradable waste